Reconstruction and renovation of worn-out residential buildings focusing on the contributory factors of social sustainability - Roohollah Taherkhani; Mitra Lotfi (مهندسی و مدیریت ساخت, 2020)
In recent years, the construction industry has had a great impact on social, economic and environmental issues, so one of the current goals of the construction industry is to reduce the negative impact on the components of sustainable development, including social, economy and environmental . Due to the increasing problems in the field of construction in the world, sustainable systems and sustainable development are among the policy priorities of developing countries, including Iran. Due to the current problems in the construction industry, Iran needs to implement solutions to solve the problems in the field of reconstruction of residential buildings with regard to sustainable development policies. Sustainable development consideration in reconstruction is not a new issue in the world, but it need to establish new policies depend on its widespread use in Iran. The reconstruction process can be considered as a capacity in sustainable development factors implementation. Eventually there will be a traditional building based on sustainable development factors. . In this research, while introducing the issue of sustainable development, the benefits and necessity of its importance and the social dimension of renovation are briefly reviewed. The social sustainability dimension factors is presented and classified